Computer safety, reliability, and security : 38th international conference, SAFECOMP 2019, Turku, Finland, September 11-13, 2019, proceedings /: 38th international conference, SAFECOMP 2019, Turku, Finland, September 11-13, 2019, proceedings. ([2019]) - Unknown
No abstract available